(untitled) (Bangladesh Journal of Botany, 2019)
Using 500 survey cards, the ethnobotanical survey was conducted over a period of 4 months. From the survey 62 species belonging to 30 families were identified. The family Lamiaceae is the most dominant followed by Apiaceae. In addition, the leaves are the most used part (38%). Furthermore, the infusion was the major mode of preparation (66%). In terms of diseases treated, digestive disorders rank first (50%), followed by respiratory diseases (28%). The results obtained will be a valuable source of information for the region. There could be a database for further research in the fields of pharmacology and for the purpose of evaluating the therapeutic efficacy of medicinal plants.